PERANCANGAN BUKU CERITA BERGAMBAR “ THE ADVENTURE OF ARA “ - Ridha Utami; hendra afriwan (Universitas Negeri Padang, 2020)
The role of parents is very important for children so they can be taught how to behave well and dare to be responsible. The purpose of designing the picture book